2013
DOI: 10.3233/jpd-130206
|View full text |Cite
|
Sign up to set email alerts
|

Memory, Mood, and Vitamin D in Persons with Parkinson's Disease

Abstract: Background Research in recent years has suggested a role of vitamin D in the central nervous system. The final converting enzyme and the vitamin D receptor are found throughout the human brain. From animal studies vitamin D appears important in neurodevelopment, up-regulation of neurotrophic factors, stabilization of mitochondrial function, and antioxidation. Objective To examine the relationship between serum vitamin D and neuropsychiatric function in persons with Parkinson’s disease (PD). Methods This is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 38 publications
2
50
1
3
Order By: Relevance
“…Further, Peterson et al concluded that, among PD patients without significant dementia, stronger performances on neuropsychiatric tests were associated with higher 25(OH)D 3 levels in the blood. This was especially true for verbal fluency and verbal memory [12]. This group also concluded that vitamin D may play a role in reducing depression [12].…”
Section: Possible Slowing Of Pd Progressionmentioning
confidence: 88%
See 3 more Smart Citations
“…Further, Peterson et al concluded that, among PD patients without significant dementia, stronger performances on neuropsychiatric tests were associated with higher 25(OH)D 3 levels in the blood. This was especially true for verbal fluency and verbal memory [12]. This group also concluded that vitamin D may play a role in reducing depression [12].…”
Section: Possible Slowing Of Pd Progressionmentioning
confidence: 88%
“…This was especially true for verbal fluency and verbal memory [12]. This group also concluded that vitamin D may play a role in reducing depression [12]. Utilizing vitamin D to improve bone health, reduce the risk of serious injury from falls, improve cognition and memory, and improve mood may lead to increased quality of life and slowed disease progression for PD patients.…”
Section: Possible Slowing Of Pd Progressionmentioning
confidence: 98%
See 2 more Smart Citations
“…Several studies with PD patients have associated vitamin D insufficiency, or variations in the vitamin D receptor, with an increased risk of developing PD (Butler et al, 2011; Evatt et al, 2008; Newmark and Newmark, 2007; Peterson, 2014); and lower levels of vitamin D have also been associated with non-motor symptoms of PD (Jang et al, 2015a; Kwon et al, 2016; Peterson et al, 2013), suggesting a possible link between vitamin D levels and PD. Additionally, a published vitamin D intervention study has demonstrated positive effects of vitamin D supplementation on clinical rating scales in PD patients (Suzuki et al, 2013), providing clinical evidence for a potential therapeutic role for vitamin D or calcitriol.…”
Section: Discussionmentioning
confidence: 99%